1994
DOI: 10.1002/ijc.2910560106
|View full text |Cite
|
Sign up to set email alerts
|

Significance of epidermal growth factor receptor expression in primary human endometrial cancer

Abstract: Radioreceptwial assessment of EGFR expression was prospectively performed on 60 primary human endometrial tumors. Of these, 26 were EGFR-positive while 13 expressed high EGFR levels. High EGFR levels correlated well with poor histopathological grading. No correlation with histopathological type, stage, myometrial invasion, lymph-node involvement or steroid hormone receptor status was observed. Disease-free survival rate was significantly shorter in the cases with high than in the cases with low EGFR levels. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…Furthermore, cell invasiveness was directly proportional to the level of EGFR expression. Similar results were obtained for patients with laryngeal squamous cell carcinoma [20], primary endometrial carcinoma [21], and laryngeal cancer [22]. In the case of primary endometrial carcinoma, Scambia et al [21] revealed that well-differentiated tumors expressed fewer receptors than moderately or poorly differentiated tumors.…”
Section: Role Of Changes In Receptor Expression Density In Health Andsupporting
confidence: 68%
“…Furthermore, cell invasiveness was directly proportional to the level of EGFR expression. Similar results were obtained for patients with laryngeal squamous cell carcinoma [20], primary endometrial carcinoma [21], and laryngeal cancer [22]. In the case of primary endometrial carcinoma, Scambia et al [21] revealed that well-differentiated tumors expressed fewer receptors than moderately or poorly differentiated tumors.…”
Section: Role Of Changes In Receptor Expression Density In Health Andsupporting
confidence: 68%
“…Most notably, deregulated EGFR activity has been linked to the development, progression and metastatic spread of HNSCC, NSCLC, CRC, breast, ovarian, cervical, bladder, pancreatic, gastric, endometrial and brain cancer. 3,[55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] In many of these cancers, EGFR expression is associated with decreased overall survival rates. 72 Modes of deregulated EGFR activity have included increased stimulation of the EGFR through ligand binding, 73 point mutations within the receptor, 74 deletion mutants of exons 2-7 of the EGFR (EGFRvIII), 75 impaired downregulation of the EGFR, 76 and gene amplification of the EGFR loci.…”
Section: The Role Of Egfr In Human Cancersmentioning
confidence: 99%
“…Similar controversies exist regarding the clinical relevance of the epidermal growth factor receptor (EGFR) in EC in general and more specifically in type II EC. EGFR expression has been demonstrated in 43 -67% of patients with endometrial cancer and its association with clinical outcome has been explored with some studies demonstrating an association between EGFR expression and poor clinical outcome (Khalifa et al, 1994;Scambia et al, 1994;Niikura et al, 1995) whereas others show no association (Reinartz et al, 1994). Moreover, the clinical role of EGFR expression specifically in type II EC has not yet been studied.…”
mentioning
confidence: 99%